2016
DOI: 10.1111/mec.13621
|View full text |Cite
|
Sign up to set email alerts
|

Distribution patterns of microbial communities in ultramafic landscape: a metagenetic approach highlights the strong relationships between diversity and environmental traits

Abstract: Microbial species richness and assemblages across ultramafic ecosystems were investigated to assess the relationship between their distributional patterns and environmental traits. The structure of microorganism communities in the Koniambo massif, New Caledonia, was investigated using a metagenetic approach correlated with edaphic and floristic factors. Vegetation cover and soil properties significantly shaped the large phylogenetic distribution of operational taxonomic unit within microbial populations, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 81 publications
(156 reference statements)
6
9
0
Order By: Relevance
“…A very recent study conducted at one site on a different isolated ultramafic Massif in New Caledonia, namely the ‘Koniambo Massif’, indicated an effect from the aboveground vegetation and edaphic parameters on microbial composition and abundance using a 454 pyrosequencing approach [82]. As previously indicated, the results obtained in the present study confirm such patterns.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A very recent study conducted at one site on a different isolated ultramafic Massif in New Caledonia, namely the ‘Koniambo Massif’, indicated an effect from the aboveground vegetation and edaphic parameters on microbial composition and abundance using a 454 pyrosequencing approach [82]. As previously indicated, the results obtained in the present study confirm such patterns.…”
Section: Discussionsupporting
confidence: 89%
“…Bacterial phyla composition showed a very high proportion of Planctomycetes. To our knowledge, such a pattern has never been observed [86,82] and could be, as for Ascomycota, an indicator of past disturbances, but that occurred there much longer ago. Furthermore, soil bacterial and fungal communities were influenced by diverse edaphic parameters as well as by the interplay between them.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…As bacteria and fungi display distinct phenotypes, phylogenies, and substrate utilization capacities, vegetation and soil properties may elicit different effects on microbial communities. Bordez et al () reported that the composition of both bacterial and fungal communities was shaped by vegetation cover rather than edaphic properties in a tropical ecosystem. In addition, edaphic properties structured mainly bacterial communities, whereas plant communities governed fungal community turnover in an old‐field chronosequence (Cline & Zak, ).…”
Section: Introductionmentioning
confidence: 99%
“…These results concur not only with studies that use cultivation-based approaches (Abou-Shanab et al, 2010;Alvarez-López et al, 2016) but also with studies based on molecular techniques using highthroughput sequencing techniques. These studies underline that these three phyla were predominant in different environments with contaminated and non-contaminated soils (Roesch et al, 2007;Buée et al, 2009b;Chu et al, 2010;Zhao et al, 2014;Bordez et al, 2016;Saad et al, 2017) but also in the rhizosphere of hyperaccumulators found in temperate climate such as Albania or Greece (Lopez et al, 2017(Lopez et al, , 2019a. Many studies suggest that Proteobacteria and Actinobacteria are the most common phyla in the rhizosphere of many plant species (Green and Bohannan, 2006;Singh et al, 2007;Kaiser et al, 2016) and bacteria belonging to these two phyla have been defined as copiotrophic (Fierer et al, 2007;Kopecky et al, 2011;Lienhard et al, 2014).…”
Section: Discussionmentioning
confidence: 98%